PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI, KEMAMPUAN BERKOMUNIKASI INTERPERSONAL, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN (STUDI EMPIRIS PADA BANK SYARIAH DI KOTA AMBON) - Ilham Habibi Zakaria; Theophilia Fina F. Leiwakabessy (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2020)
ABSTRACT This was study aimed to examined the effect of the use of information technology, interpersonal communication skills, and leadership styles on employee performance at Islamic Banks in Ambon City. The population of this research are all employees at three Islamic banks in Ambon City.Sampling was conducted using a purposive sampling and number of samples are 65 respondents. Technique of data collection is survey by using questionnaires. Analysis using multiple regression analysis. The results showed that the use of information technology had a positive and significant effect on employee performance. While interpersonal communication skills and leadership style variables do not significantly affect on employee performance. Keywords: Information Technology, Interpersonal Communication Ability, Leadership Style,and Employee Performance